PENGEMBANGAN MEDIA “KLIK AJA” DALAM PEMBELAJARAN DARING MENYAMPAIKAN TEKS BERITA BAGI SISWA KELAS VIII (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
The Covid-19 pandemic is a new challenge in the world of education, especially for a teacher, because learning must be done online. Therefore, teachers must master digital skills and creative thinking patterns, especially in conveying news texts. Facing this, this study discusses the development of online-based interactive learning media. The media development was designed by utilizing the Articulate Storyline 3 software in collaboration with learning videos and Google forms which were then combined on the Linktree website. The objectives of this study include describing the development of media and the presentation/display of the "Click Aja" media in online learning to deliver news texts for class VIII students and describe the results of the effectiveness test of using "Click Aja" media in online learning to deliver news texts for class VIII students. This study uses the type of research and development method ADDIE model. Through this research method, the discussion in this study leads to the resulting product, which is a "Click Aja" learning media. The product was tested by experts and obtained an average value of 3.4 which states that the media is suitable for use. In addition, the product was also tested on students and obtained an average score of 3.51 which stated that the media was suitable for use. Although the "Click Aja" media is feasible to use, there are improvements submitted by experts, including errors in writing, the delivery of material in the learning video is less communicative and incomplete material regarding news texts.